Globalization and Awka Personal Names: An Anthropolinguistic Study - Udoye, Ifeoma Emmanuela (NIU Journal of Humanities; Vol 4 No 1 (2019): KIU Journal of Humanities, Vol. 4 No. 1, March 2019, 2019)
This paper examines the effect of globalization and modernity on Awka personal names from anthropolinguistic perspective. Ten names were given in-depth analysis based on primitivism theory by Lovejoy and Boas (1935). The study indicates that most Awka names tell stories about the people. Through names, it is possible to understand the Awka manâ€™s  simple way of life. Finally, it is discovered that globalization has destroyed most of the indigenous names making the people to embrace English names or names that do not reflect their culture and tradition because the people believe that such names will help them to keep abreast with the modern times. Keywords: Globalization, Awka, names, culture, primitive, Ozo